Merchants of Virtue : Herman Miller and the Making of a Sustainable Company - Birchard, Bill (New York Palgrave Macmillan, 2011)
Merchants of Virtue is about the company Herman Miller and a band of people who determined to make their company a good global citizen. They end up answering one of the critical questions of our time: Is sustainable business sustainable? Can employees in global companies make great products, take care of the environment, benefit society, and make good money-all at the same time, good times and bad? Merchants of Virtue tells this story from the point of view of Murray and other people who made the changes. It does not simply recount the story of a CEO who, by dint of power, commanded a sea change in business. It instead tells of researchers and designers and engineers and factory bosses who made great things happen in back rooms and on the factory floor. These people, across the ranks, joined to advance a revolution. They reached new insights, recast policies, changed behaviors, and redesigned management. They also changed the people around them-and they can change all of us"
Include Illustration and Index
Keywords: Social responsibility of business -- Strategic planning--Environmental aspects -- Sustainable development